Design vernacular: um registro de artefatos produzidos por artesãos da aldeia hippie (Arembepe-Ba) - Moraes, Bruna Roberta Velame (2023)
This research is an investigation into the technologies used in the design of popular artifacts produced by artisans from Aldeia Hippie, located in Arembepe, in the municipality of Camaçari-BA. This artisanal knowledge linked to the Hippie counterculture movement (1960s) historical context where the Village was born, is considered a cultural heritage. Through photographic records, it understands how such objects reflect local knowledge and practices. This research aims at analyzing the relationship between Design, Culture and Technology established in the hippies' artifacts, registering, and disseminating popular knowledge from their material culture, imaginary and social belonging. The research problem of this research is: What is the relationship between design, culture and technology established in the artifacts of the hippies of the Aldeia in Arembepe-BA? The methodology is based on the documentary research analysis method, using theoretical references about vernacular design and analysis of hippie artifacts collected in the community. Furthermore, the popular artifacts created by the community addressed in this research are understood not only as mere handicrafts, but as a symbolic activity that expresses the knowledge and practices of this people in a technical creative process of design. Reproduced from the habits and memories that these individuals experience, express and produce their ideas on a daily basis and that justify their recognition and cultural perpetuation